Fungicide sensitivity and genetic structure of the population of Alternaria grandis - Silva, Rhaphael Alves (2022)
Early blight (EB), caused by Alternaria grandis, A. linariae, or A. solani, is a severe disease of potato and tomato crops and fungicide application is the most used strategy to reduce yield losses. This study was conducted to: i. identify Alternaria spp. associated with EB of potato and tomato; ii. develop SSR markers for the dominant species causing potato EB; iii. assess the genetic variability of the population of the predominant species; and iv. assess the sensitivity of the pathogen to SDHIs, DMIs, and chlorothalonil (CT). A. grandis and A. linariae were the predominant species associated with EB of potato and tomato, respectively. Twelve SSR markers were designed for A. grandis and 302 isolates were genotyped to assess the genetic structure of the pathogen population. A total of 253 MLLs were identified. The population of A. grandis has high genetic variability, but no structure could be detected. Fungicide sensitivity was assessed using two methods: the microtiter method for SDHIs (BosCalid; FluoPyram; FluXapyroxad; PydiFlumetofen; and PenthioPyrad); and mycelial growth on fungicide-amended medium for difenoconazole (DC) and CT. Additionally, discriminatory doses (DD) were established for high-throughput screening of isolates. The EC50 values for CT and DC ranged from 109.3 to 905.4 and 0.03 to 2.27 µg/mL, respectively, and the DD for CT and DC were 1000 µg/mL and 5 µg/mL, respectively. There is no evidence of resistance to DC, but there are isolates less sensitive to CT. The EC50 values of BC, FP, FX, PF, and PP ranged from 0.3 to 0.8; 0.9 to 69.7; 0.6 to 11.3; 0.2 to 92.5; and 6.7 to 61.5 µg/mL, respectively, and the DD were 100, 25, 25, 10, and 25 µg/mL, respectively. The sensitivity to SDHIs of 113 isolates was assessed using the DD. For BC, all isolates were classified as insensitive; for PP, FX, FP, and PF, 94%, 89%, 63%, and 61% were classified as insensitive to the respective fungicides. The reduced sensitivity of A. grandis to BC, FX, and PP fungicides is probably associated with the widespread occurrence of the H278Y and H134R mutations in the sdhB and sdhC genes, respectively. Management of EB must employ multi-site fungicides and site-specific products with different modes of actions. Keywords: Alternaria spp.. Genetic variability. Multi-site fungicides.